Crítical thinking and intercultural philosophy - VIAÑA RUBIO, Carlos; VILLANUEVA BARRETO, Jaime (Utopía y Praxis Latinoamericana, 2022)
This article aims to show the inextricable relationship between critical thinking and interculturality. It tries to answer the challenging question launched by Raúl Fornet-Betancourt about what critical thinking should be critical of, in order to explore the answer he himself offers: with the contemporary world. It is proposed in this paper to show that intercultural philosophy stands as the spokesman of that critical thinking that challenges the neoliberal hegemony of the capitalist and monocultural West. To do so, we base ourselves on the philosophical proposal of Fornet-Betancourt to advance from there to some characterizations of critical thinking as that which goes beyond simplifications and rather serves as an instrument to establish an intercultural dialogue with other ways of understanding the world. We explore the Andean proposal of Sumak Kawsay as an expression of critical thinking that questions, from a millenary knowledge and civilization, the very bases of Western developmentalism.